2010
DOI: 10.1590/1808-1657v77p3892010
|View full text |Cite
|
Sign up to set email alerts
|

Aspectos Epidemiológicos Da Tuberculose Caprina Na Mesorregião Do Triângulo Mineiro E Alto Paranaíba, Mg

Abstract: RESUMO Dados referentes à tuberculose caprina no Brasil e sua importância em saúde pública são escassos. Diante disso, este trabalho teve por objetivos investigar a ocorrência e pesquisar aspectos epidemiológicos da tuberculose em rebanhos leiteiros caprinos na mesorregião do Triângulo Mineiro e Alto Paranaíba, MG. Foram tuberculinizados 233 caprinos provenientes de sete propriedades leiteiras, utilizando-se o teste cervical comparativo, tomando-se como referência os procedimentos e critérios de interpretação … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
1
0
0
Order By: Relevance
“…These authors attributed the prevalence, among other things, to the use of management without proper technical instructions. Data similar to this study were found by BOMBONATO et al (2010), in the state of Minas Gerais, where 233 goats were submitted to tuberculin skin test by the comparative cervical test, and a prevalence of 1.29% (3/233) was found. Low prevalence for tuberculosis in small ruminants (0.9% in sheep and 2.4% in goat), were found by JAVED et al (2010) that the sample utilized, the geographical features, and the particular situation of each studied property could explain the differences between the prevalence observed in many studies.…”
Section: Resultssupporting
confidence: 89%
“…These authors attributed the prevalence, among other things, to the use of management without proper technical instructions. Data similar to this study were found by BOMBONATO et al (2010), in the state of Minas Gerais, where 233 goats were submitted to tuberculin skin test by the comparative cervical test, and a prevalence of 1.29% (3/233) was found. Low prevalence for tuberculosis in small ruminants (0.9% in sheep and 2.4% in goat), were found by JAVED et al (2010) that the sample utilized, the geographical features, and the particular situation of each studied property could explain the differences between the prevalence observed in many studies.…”
Section: Resultssupporting
confidence: 89%